High level of hemoglobin, white blood cells and obesity among Sudanese women in early pregnancy: a cross-sectional study. (4th April 2017) - Elmugabil, Abdelmageed; Rayis, Duria A; Abdelmageed, Renda E; Adam, Ishag; Gasim, Gasim I
Aim: To investigate the association between obesity and anemia/hemoglobin levels.Material & methods: A cross-sectional study was conducted at Khartoum, Sudan. Obstetric data were collected from 388 pregnant women at mean (standard deviation) of 10.5 (3.1) weeks of gestation using questionnaires. Weight and height were determined, and BMI was calculated.Results: There were 15 (4.4%), 95 (28.1%), 127 (37.6) and 101 (29.9%) women who were underweight, normal weight, (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ) and obese (≥30 kg/m 2 ), respectively. Hemoglobin levels and white blood cell counts were significantly higher in obese than nonobese groups. Compared with normal BMI, overweight and obesity were associated with higher hemoglobin level.Conclusion: Obese women had higher white blood cell count and hemoglobin level. Lay abstract: Obesity during pregnancy has many maternal and perinatal adverse effects. The current study was conducted to investigate the association between obesity, hemoglobin level and white blood cell count among pregnant Sudanese women in their early pregnancy. Around a third of the 388 women were obese. Hemoglobin level and white blood cells count were significantly higher in obese than nonobese women. Further studies are needed to fully understand the implications of this relationship.